PACE Manual Procedures. - African Union Inter-African Bureau for Animal Resources; AU-IBAR (My University, 2021)
Animal health is a prior condition for the development of livestock farming and the rural world in Africa where, despite meat imports in particular, the population does not get proper amounts of animal protein. Animal diseases are one of the main reasons for this shortage because of their direct effects on livestock — mortality, drops in production etc. In addition the current situation of health insecurity discourages investment in the sector. Epizootics as a constraint to trade in animal products. The Pan-African Rinderpest Campaign (PARC) has been co-financed by the European Community (EC) since 1986. It has already done a great deal to improve animal health security by combating rinderpest, one of the most devastating contagious diseases of cattle. PARC's positive results, confirmed by an independent evaluation in 1996/97, offer a firm basis for eradicating rinderpest and controlling other major diseases. The idea behind the PACE Programme is to build on the headway made in the campaign against rinderpest in order to establish lower-cost national and continental epidemiological surveillance networks for the main animal diseases, provide the countries with the capacities needed to organise economically and technically justified control programmes and develop effective and sustainable distribution of veterinary products and services. The five-year PACE programme will cover 32 sub-Saharan African countries. It will be coordinated by the Interafrican Bureau for Animal Resources (IBAR) of the Organisation of African Unity (OAU). A participatory approach will be adopted so that livestock farmers and animal health professionals will be involved in implementing the programme. All animal product consumers will benefit from the PACE Programme, as well as the national economies of the participating countries. The programme will include national operations planned and implemented in each country and also sub-regional and regional support and coordinatica components. By creating an appropriate health security framework, the PACE programme will remove one of the major constraints on the development of the livestock fanning sector. It will thus help to improve farmers' incomes and people's general living conditions. Other programmes can be developed to back up these activities, for example in support of the necessary increases in animal productivity. Its financial return will be at least 19% in 10 years and the transfer of technical capacity on the ground will ensure that its effects are sustainable. The total cost of the programme is EUR 72 million, some 74% for the national components and 26% for services common to the various countries (regional component), including contingencies. It will last for five years.
Keywords: Pan-African Control of Epizootics (PACE)